2014
DOI: 10.1017/s0950268814000892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of HIV infection and sexually transmitted infections in female sex workers (FSWs) in Shanghai, China

Abstract: In 2009, we examined HIV and sexually transmitted infections (STIs) in 750 female sex workers (FSWs) in Shanghai using a cross-sectional survey. Participants (mean age 27 years) were interviewed and tested for HIV and selected STIs. Prevalence was: HIV 0·13%, chlamydia 14·7%, gonorrhoea 3·5% and syphilis 1·3%. In a demographic multivariate model, younger age, higher income and originating from provinces other than Zhejiang and Shanghai were independently associated with STI. In a social and sexual behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…Categoria temática Síntese do conhecimento (n=17) Caracterização da MPS Os artigos mostram as características da MPS em relação aos aspectos sociodemográficos (idade, local de atuação, valor do programa) e comportamentais (início da atividade sexual, uso de drogas, número de parceiros sexuais, tipo de prática, tipo de parceria (fixo ou casual) (3)(4)10,12,18) . Prevalência de Sífilis, fatores associados e coinfecção A prevalência de sífilis variou de 0,1% a 35,4% (1-2-3-4-8-9-10-11-12-13- 14-15-16-17-18-19) .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Categoria temática Síntese do conhecimento (n=17) Caracterização da MPS Os artigos mostram as características da MPS em relação aos aspectos sociodemográficos (idade, local de atuação, valor do programa) e comportamentais (início da atividade sexual, uso de drogas, número de parceiros sexuais, tipo de prática, tipo de parceria (fixo ou casual) (3)(4)10,12,18) . Prevalência de Sífilis, fatores associados e coinfecção A prevalência de sífilis variou de 0,1% a 35,4% (1-2-3-4-8-9-10-11-12-13- 14-15-16-17-18-19) .…”
Section: Resultsunclassified
“…A presença de infecções por sífilis, também, pode estar associada a outras infecções como clamídia 7% e gonorréia 3,5% em 7500 MPS na China (4) . Pesquisa nacional realizada no sudeste do país, mostrou que 102 MPS obtiveram uma prevalência de IST de 71,6%, sendo que os maiores valores encontrados foram para o HPV 67,7% e infecção clamidiana 20,5% (20) .…”
Section: Medidas Interventivasunclassified
See 1 more Smart Citation
“…In the meantime, there were 7335 clinics to serve Voluntary Counseling Testing (VCT) and 1,630,926 received counseling, of them 1,605,079 were tested for HIV antibody. Specifically, since 2005 the Ministry of Health in China cooperated with UNAIDS, WHO, US CDC, and other international organizations to jointly release "Update on the HIV Epidemic and Response in China" every two years, from which according to the estimation of HIV/AIDS the cumulative number of PLHIV was 650,000 in 2005, 700,000 in 2007, 740,000 in 2009, and 780,000 in 2011, respectively [12][13][14][15][16][17][18][19].…”
Section: Focusing On Professionalmentioning
confidence: 99%
“…Previous studies have documented that a majority of older HIV/STI cases in China reported a history of commercial sex with mid-age female sex workers (FSWs) who were over 35 years [30, 31]. Research in China and other developing countries have examined the epidemic of syphilis and its potential determinants among predominantly young FSWs who are younger than 35 years [3234]. However, findings from these studies may not apply to mid-age FSWs as they may have different behavioral risk factors for HIV/STIs.…”
Section: Introductionmentioning
confidence: 99%